2023
DOI: 10.3390/clinpract13020030
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenic Effects of Areca Nut and Its Metabolites: A Review of the Experimental Evidence

Abstract: Oral cancers (OC) are among the most frequent malignancies encountered in Southeast Asia, primarily due to the prevalent habit of betel quid (BQ) and smokeless tobacco use in this region. Areca nut (AN), the primary ingredient in BQ, contains several alkaloids, including arecoline, arecaidine, guvacoline, and guvacine. These have been associated with both the AN abuse liability and carcinogenicity. Additionally, variations in AN alkaloid levels could lead to differences in the addictiveness and carcinogenic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 140 publications
0
8
0
Order By: Relevance
“…One of the major factors is thought to be the use of betel nut in the SA culture, which is commonly consumed in the form of betel quid. Although the added tobacco plays a significant role in the development of OSCCs, studies have suggested that betel products, which contain arecoline and 3-(methylnitrosamino) propionitrile, may have an independent carcinogenic effect (35) resulting in malignant transformation of oral submucosal fibrosis (OSMF). The potential for malignant transformation resulting in OSCC has been reported to be as high as 7 to 13% (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major factors is thought to be the use of betel nut in the SA culture, which is commonly consumed in the form of betel quid. Although the added tobacco plays a significant role in the development of OSCCs, studies have suggested that betel products, which contain arecoline and 3-(methylnitrosamino) propionitrile, may have an independent carcinogenic effect (35) resulting in malignant transformation of oral submucosal fibrosis (OSMF). The potential for malignant transformation resulting in OSCC has been reported to be as high as 7 to 13% (36).…”
Section: Discussionmentioning
confidence: 99%
“…Univariate Kaplan-Meier analysis revealed that patients of SA ethnicity had worse RFS [HR=2. 35 (1.51-3.65)] than those of non-SA ethnicity (Figure 2A). RFS for SA patients at 3-year follow up was 52%, compared to 76% in the non-SA group (p<0.01).…”
Section: Recurrence Free Survivalmentioning
confidence: 95%
“…6 Oral cancer can be influenced by various factors such as excessive tobacco consumption (both smoked and smokeless forms), betel nut chewing, alcohol, and chronic inflammation. 7,8 Human papillomavirus-related (mostly HPV16) oral and oropharyngeal malignancies have become more common in young people in recent decades. [9][10][11] In the realm of oncology, chemotherapy is the anticancer therapy that is most frequently used.…”
Section: Introductionmentioning
confidence: 99%
“…Oral cancer incidence rises with age, peaking in persons over 60 and among those under 40 years 6 . Oral cancer can be influenced by various factors such as excessive tobacco consumption (both smoked and smokeless forms), betel nut chewing, alcohol, and chronic inflammation 7,8 . Human papillomavirus‐related (mostly HPV16) oral and oropharyngeal malignancies have become more common in young people in recent decades 9–11 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, China stands as the second-largest producer of areca nut globally 3 . Despite its popularity, areca nut is classi ed as carcinogenic to humans and has been linked to a range of detrimental health effects, including carcinogenicity 4 , genetic and epigenetic instability 5 , sub-mucous brosis progression 6 , oral cancer 7 , and liver disease 8 .…”
Section: Introductionmentioning
confidence: 99%